Does auditor tenure improve audit quality? - Tan, Hun Tong. (2008)
In this study, we provide evidence that the relation between auditor tenure and audit quality, proxied by discretionary accruals and earnings response coefficients, is conditional on auditor specialization and client importance (in terms of economic contribution to the public accounting firm’s income). We find that longer audit tenure is associated with higher audit quality in the case of firms audited by specialists that have low fee dependence on clients, but that the tenure-audit quality relation is either weaker or absent in the case of firms audited by non-specialists and/or those where the auditor has a high fee dependence. These results indicate that benefits of long auditor-client relationship in improving audit quality are greatest when the auditor has industry knowledge and lower economic bonding with the client.